Unexpected Victory: High-Risk Papillary Thyroid Cancer with Distant Metastases Shows Extraordinary Response to First RAI Treatment - Muntaha Fatima Rana; Fatima Ibrahim; Aamna Hassan (Journal of the Pakistan Medical Association, 2024)
Papillary Thyroid Cancer (PTC) is the most prevalent type of differentiated thyroid cancer. Its incidence is growing worldwide although it has low death rates. Treatment includes surgery followed by radioactive iodine therapy. Patients are followed up with serum tumour markers (stimulated and unstimulated), sonographically and with iodine I-131 whole body scans. Patients with aggressive metastatic disease have worse prognosis as compared to those with localized disease. We present a case of high-risk PTC with lung metastases, who showed excellent response after the first radioactive iodine therapy. Keywords: Thyroid cancer, lung metastases, excellent response.